2005
DOI: 10.1017/s0021859605005277
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic evaluation and performance of flax varieties for industrial fibre production

Abstract: Flax fibre for industrial purposes differs from that for linen production, although the agronomic factors that influence fibre development and which factors are most important for industrial fibre production have still to be defined. A description of variations in the performance of fibre flax varieties is also necessary as current guidance relates to the European market rather than the UK. Field trials were sown in 2002 and 2003 at the Henfaes Research Centre in north Wales, investigating 29 and 26 varieties,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
2
8
0
1
Order By: Relevance
“…The differences between linseed varieties in seed yield per ha might be attributed to their differences in growth traits such as number of fruiting branches reflected differences in yield components such as number of capsule per plant as well as 1000-seed weight and hence increased seed yield per plant as well as per unit area. The results are in agreement with the findings of El-Shimy et al (2001), El-Shimy et al (2002), Dimmock et al (2005) and Hussein (2007) and they observed that flax genotypes significantly differed in number of capsules per plant and finally seed yield per hectare. Among the four linseed varieties, T-397 exerted first promising yield attributing characters (mainly capsule per plant) during investigation, which reflected in seed yield.…”
Section: Resultssupporting
confidence: 92%
“…The differences between linseed varieties in seed yield per ha might be attributed to their differences in growth traits such as number of fruiting branches reflected differences in yield components such as number of capsule per plant as well as 1000-seed weight and hence increased seed yield per plant as well as per unit area. The results are in agreement with the findings of El-Shimy et al (2001), El-Shimy et al (2002), Dimmock et al (2005) and Hussein (2007) and they observed that flax genotypes significantly differed in number of capsules per plant and finally seed yield per hectare. Among the four linseed varieties, T-397 exerted first promising yield attributing characters (mainly capsule per plant) during investigation, which reflected in seed yield.…”
Section: Resultssupporting
confidence: 92%
“…However, for stem diameter most of the variance associated with sites was due to interaction with the treatments, particularly seeding date, and not the overall effect of site (Table 2). Dimmock et al (2005) also found a large year impact on fibre yield. Analysis of the straw from these trials showed that 96% of the variation in fibre fineness was due to year effect and that fine fibres occurred with fibre yields were lower (Norton et al 2006).…”
Section: Discussionmentioning
confidence: 84%
“…Principal components were constructed using the correlation matrix. For a detailed method and discussion of the use of PCA in cultivar trials see Dimmock et al (2005).…”
Section: Post-harvest Management and Laboratory Analysismentioning
confidence: 99%
“…Multivariate analysis of phenotype measurements has proved useful for examining barley diversity (Murphy and Witcombe 1981;Murphy and Witcombe 1986;Witcombe 1975) and it is a powerful method for investigating agronomic performance of non-adapted novel crop germplasm, as recently demonstrated through the evaluation of continental European-bred flax cultivars in Wales (Dimmock et al 2005).…”
Section: Introductionmentioning
confidence: 99%